Microcomputed analysis of nerve angioarchitecture after combined stem cell delivery and surgical angiogenesis to nerve allograft. Issue 8 (August 2021) - Saffari, T.M.; Mathot, F.; Thaler, R.; van Wijnen, A.J.; Bishop, A.T.; Shin, A.Y.
Summary: Introduction: A detailed three-dimensional (3D) evaluation of microvasculature is evolving to be a powerful tool, providing mechanistic understanding of angiomodulating strategies. The aim of this study was to evaluate the microvascular architecture of nerve allografts after combined stem cell delivery and surgical angiogenesis in a rat sciatic nerve defect model. Materials and Methods: In 25 Lewis rats, sciatic nerve gaps were repaired with (i) autografts, (ii) allografts, (iii) allografts wrapped in a pedicled superficial inferior epigastric artery fascia (SIEF) flap to provide surgical angiogenesis, combined with (iv) undifferentiated mesenchymal stem cells (MSC) and (v) MSCs differentiated into Schwann cell-like cells. At two weeks, vascular volume was measured using microcomputed tomography, and percentage and volume of vessels at different diameters were evaluated and compared with controls. Results: The vascular volume was significantly greatest in allografts treated with undifferentiated MSCs and surgical angiogenesis combined as compared to all experimental groups ( P <0.01 as compared to autografts, P <0.0001 to allografts, and P <0.05 to SIEF and SIEF combined with differentiated MSCs, respectively). Volume and diameters of vessel segments in nerve allografts were enhanced by surgical angiogenesis. These distributions were further improved when surgical angiogenesis was combined with stem cells, with greatest increase found when combined with undifferentiated MSCs. Conclusions: The interaction between vascularity and stem cells remains complex, however, this study provides some insight into its synergistic mechanisms. The combination of surgical angiogenesis with undifferentiated MSCs specifically, results in the greatest increase in revascularization, size of vessels, and stimulation of vessels to reach the middle longitudinal third of the nerve allograft.